(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In her first novel, The Tiger’s Daughter(1971), Mukherjee uses the return to India of her nostalgic and ’homesick’Bengali Brahmin heroine as the context for undermining national myths oforigins and foundations. In other words, the migrant’s return ’to recover herroots’ and the stability of her cultural identity as an Indian is not equateduncritically with an unexamined sense of what being ’Indian’ means. Instead,Mukherjee uses the migrant’s moment of return to elaborate a much more complexand mediated understanding of national and cultural identity.